Class in the composition classroom: pedagogy and the working class - Carter, Genesea M., editor; Thelin, William H., editor; Utah State University Press, publisher (Colorado State University. Libraries, 2017)
What college writing instructors should know about working-class students--their backgrounds, experiences, identities, learning styles, and skills--in order to support them in the classroom, across campus, and beyond. Contributors explore the nuanced and complex meaning of "working class" and the values these writers bring.--Provided by publisher.
Pedagogy at the crossroads: intersections between instructor and student identities across institutional contexts / Aubrey Schiavone and Anna V. Knutson -- No homo!: toward an intersection of sexuality and masculinity for working-class men / Robert Mundy and Harry Denny -- Implications of re-defining "working class" in the urban composition classroom / Aaron Barlow and Patrick Corbett -- California dreams: working-class writers at the California State University system / Cassandra Dulin -- The writing space as dialectical space: disrupting the pedagogical imperative to prepare the 'underprepared' / Jacqueline Preston -- Changing definitions of work and class in the information economy / Edie-Marie Roper and Mike Edwards -- Telling our story: 'college writing' for trade unionists / Rebecca Fraser -- Emotional labor as imposters: working-class literacy narratives and academic identities / Nancy Mack -- We're all middle class? students' interpretation of childhood ethnographies to reflect on class difference and identity / Liberty Kohn -- Pedagogies of interdependence: writing as advocacy / Holly Middleton -- Never and forever just keep coming back again: class, access, and student writing performance / Missy Nieveen Phegley -- Social economies of literacy in rural Oregon: accounting for diverse sponsorship histories of working-class students in and out of school / Cori Brewster -- Rethinking 'class': poverty, pedagogy, and two-year college writing programs / Brett Griffiths and Christie Toth -- Retrograde movements and the educational encounter: working-class adults in first-year composition / James E. Romesburg -- "Being part of something gave me purpose": how community membership impacts first-year students' sense of self / Genesea M. Carter -- Literacy development as social practice in the lives of four working-class women / Gail G. Verdi and Miriam Eisenstein Ebsworth.
Keywords: Working class -- Education (Higher); College students' writings; Classroom environment; English language -- Composition and exercises -- Study and teaching